2020
DOI: 10.1080/21551197.2019.1707740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of New Zealand Blackcurrant on Blood Pressure, Cognitive Function and Functional Performance in Older Adults

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…While current crossover studies are limited (Table 7), the mechanisms through which blackcurrant supplementation may regulate vascular tone are well understood. More studies need to be conducted in human populations, both in an acute and chronic setting, to corroborate the findings of Cook et al [44] and establish ideal dosage for chronic studies.…”
Section: Hypertensionmentioning
confidence: 77%
See 4 more Smart Citations
“…While current crossover studies are limited (Table 7), the mechanisms through which blackcurrant supplementation may regulate vascular tone are well understood. More studies need to be conducted in human populations, both in an acute and chronic setting, to corroborate the findings of Cook et al [44] and establish ideal dosage for chronic studies.…”
Section: Hypertensionmentioning
confidence: 77%
“…The potential effects of blackcurrant anthocyanins on hypertension are currently not well established (Table 7). However, a recent study [44] showed that ingestion of 600 mg/day of anthocyanins from a NZ blackcurrant extract over a 7 day intervention period resulted in decreases in systolic (6 mmHg) and diastolic (6 mmHg) blood pressure in a cohort of 14 healthy older adults. Such changes are sufficient to improve health outcomes.…”
Section: Hypertensionmentioning
confidence: 98%
See 3 more Smart Citations